2018
DOI: 10.1074/jbc.ra118.002104
|View full text |Cite
|
Sign up to set email alerts
|

Cullin-3–RING ubiquitin ligase activity is required for striated muscle function in mice

Abstract: Control of protein homeostasis is an essential cellular process that, when perturbed, can result in the deregulation or toxic accumulation of proteins. Owing to constant mechanical stress, striated muscle proteins are particularly prone to wear and tear and require several protein quality-control mechanisms to coordinate protein turnover and removal of damaged proteins. Kelch-like proteins, substrate adapters for the Cullin-3 (Cul3)-RING ligase (CRL3) complex, are emerging as critical regulators of striated mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
5
26
0
Order By: Relevance
“…5c and Supplementary Table 4). Overall, and in agreement with previous observations 30-32 , the observed fold changes were mild, in line with the hypothesis that the ubiquitylated isoform of a protein represents only a small fraction of the total pool of that given protein at any time point 33 . We noticed, however, that proteins with abnormal levels in Cul3 homozygous mutants are significantly enriched for high confidence ASD-risk genes ( Cul3 fl/fl Emx1-Cre at 20% FDR, 65 genes, p= 0.0329).…”
Section: Resultssupporting
confidence: 92%
“…5c and Supplementary Table 4). Overall, and in agreement with previous observations 30-32 , the observed fold changes were mild, in line with the hypothesis that the ubiquitylated isoform of a protein represents only a small fraction of the total pool of that given protein at any time point 33 . We noticed, however, that proteins with abnormal levels in Cul3 homozygous mutants are significantly enriched for high confidence ASD-risk genes ( Cul3 fl/fl Emx1-Cre at 20% FDR, 65 genes, p= 0.0329).…”
Section: Resultssupporting
confidence: 92%
“…During preparation of the present manuscript, an article investigating the role of Cullin-3 in striated muscles was published (20). The authors demonstrated that Cullin-3 was required for striated muscle development, a finding that our studies fully support.…”
Section: Introductionsupporting
confidence: 56%
“…KLHL9 (Cirak et al, ), KBTBD13 (Sambuughin et al, ), KLHL40 (Ravenscroft et al, ), and KLHL41 (Gupta et al, ) have been implicated in distal and nemaline myopathy. CUL3 is enriched in muscle tissues, essential for myoblast differentiation, and conditional CM‐KO of CUL3 is neonatal lethal in mice (Blondelle, Shapiro, Domenighetti, & Lange, ; Papizan et al, ). CM deletion of NAE1, a regulatory subunit of neddylation, in mice CMs caused heart failure and perinatal lethality (Zou et al, ).…”
Section: Discussionmentioning
confidence: 99%